Development of Jombang Local Cultural Diversity Educative Games Science Material for Class IV Studens of SDN Mojojejer 2 Jombang - Zakaria, Afif Fadhilah; Harsiwi, Nova Estu (eductum: Jurnal Literasi Pendidikan, 2025)
The aims of this research and development, are: (1) To develop valid learning media of Educational Games on Local Cultural Diversity in Jombang based on expert validation. (2) To develop effective learning media of Educational Games on Local Cultural Diversity in Jombang based on learning implementation sheets (teacher and student activities) and student cognitive learning outcomes. (3) To develop interesting learning media of Educational Games on Local Cultural Diversity in Jombang based on student and teacher response questionnaires. This research is a research and development that refers to the ADDIE model (analyze, design, development, implementation, evaluation). Based on the results of the research that has been carried out, the percentage of validity of the Jombang Local Cultural Diversity Educational Game learning media is obtained in terms of the results of the media expert validator 90%, the language expert validator 93%, the material expert validator 97% with all three in the category "very valid", and the results of the learning design expert validator 78% with the category "valid". The average value of media validity is 89.75% with the category "very valid". The effectiveness of the Jombang Local Cultural Diversity Educational Game learning media in terms of classical learning outcomes is 100% with the criteria "complete", the percentage of teacher activity value is 89% with the category "very active" and the percentage of student activity value is 88% with the category "very active". The attractiveness is reviewed from the teacher's response, obtaining a percentage value of 97% and the student's response obtaining a value of 97.3% with each being in the category "very attractive". Based on the results obtained, the Development of Educational Games on Local Cultural Diversity in Jombang at IPAS Material for IVth Grade Students of SDN Mojojejer 2 Jombang is valid, effective and attractive.